دلالة الكلمة وتطورها في المثل السائر - ندى سامي ناصر (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
Scientists consider the human language is like the living being, it lives on the tongues of who speak it from the a lives, it is therefore evolving and changing by time as the human being develops and changes and it is subject to growth rules development. Language is also a social phenomenon, because it lives in the society, derives its being from it, and develops as it develops, Language like other social phenomena, it's subject to steady evolution in its various components: Their voices, grammars, meanings and their implications, this development is subject in its course to clear and fixed laws and no one can stop or change their results. Semantic development is one of the aspects of linguistic development, the field of words and meanings and the meanings of words do not settle on the same situation but it's in constant nonstop change, reading one of the Arabic dictionaries and books of ancient linguists prove this development and found that the meanings of words change from time to time, the development of semantic various factors lead to this change and it has certain aspects of this development which is what we are trying to study it through this research.